Heterozygous Deletion of Macro Domain Containing 2 (MACROD2) is Associated with Autism Spectrum Disorder - Frye, Richard E; Tippett, Marie; Delhey, Leanna; Slattery, John (North American Journal of Medicine and Science, 2016)
Autism Spectrum Disorder (ASD) is associated with genetic abnormalities in many cases, including common genetic syndromes, copy number variations, and rare genetic mutations. Studies have associated the 20p12.1 region and the Macro Domain Containing 2 (MACROD2) gene with ASD but this region or gene has not been specifically reported in an ASD case. In this case report we describe a non-syndromic boy with mild-to-moderate ASD who was found to have a deletion in the 20p12.1 region affecting only the MACROD2 gene. Other causes of ASD, including neurologic, metabolic and nutritional disorders, could not be identified. Given that this gene has been shown to be expressed in the ventricular zone of the brain during embryonic development, is associated with several neurologic and psychiatric disorders and has several associations with ASD, it may be an excellent candidate gene for non-syndromic ASD.